The prevalence of low energy availability risk in New Zealand athletes : a thesis presented to Massey University in partial fulfilment of requirements for the degree of Master of Science (MSc) in Nutrition and Dietetics - Fenton, Eliot Rhys (Massey University, 2022)
Background: Low energy availability (LEA) is a state in which an individual has insufficient energy to maintain and support normal physiological functions. This is often influenced by changes in energy intake (EI) or energy expenditure through exercise (EEE). Low energy availability is the aetiology of the syndrome relative energy deficiency in sports (RED-S) and the female athlete triad (FAT). Together, these models encapsulate the effects upon physiological systems such as menstrual, psychological, haematological, metabolic, and endocrine function, and bone health, to label a few. To date, LEA research predominately focuses on females and endurance sports athletes. There is minimal research on male athletes or high-intensity sports, such as sprinting. Methods: A total of 24 amateur-elite athletes (males, n =10; females, n =14) aged 16–35 years participated in this cross-sectional study. All participants competed in at least one athletic track event (100m, 200m, 400m, 800m, 1500m, 3000m, 5000m, steeplechase and hurdles) in the 2019/20 or 2020/2021 athletic seasons. The risk assessment for LEA was determined online through a validated screening tool (low energy availability questionnaire (LEAF-Q)) for females and an arrangement of three validate questionnaires (Sexual desire inventory, Androgen deficiency in males and gastrointestinal questions from LEAF-Q) aimed at assessing key LEA measures for males such as sexual desire, mood and gastrointestinal function. These LEA-assessing questionnaires were a part of a larger online questionnaire to identify key risk factors and physiological outcomes of LEA (e.g., sleep behaviour and qualities, eating disorder risk, exercise dependence). Results: This study determined 57% (n = 8) of female participants and 50% (n = 5) of male participants were at risk of LEA. This study observed that females at risk of LEA had significantly poorer sleep behaviours (p <0.05), higher depression score and eating disorder examination (EDE) global score than those females not at risk of LEA. Results showed trends that males not at risk of LEA were more likely to have better sleep scores (d = -0.87). In the EDE males not at risk of LEA had lower eating concern (d = -0.86), body shape concern (d = - 0.95), weight concern (d = -0.94) and risk of global eating disorder examination (d = -0.8). In the exercise dependence scale males not at risk of LEA showed a higher tolerance (d = 1.1), continuance (d = 0.88), lack of control (d = 0.65) and lower intentions of effect (d = - 0.94). Whereas female athletes not at risk of LEA tended to be less likely to display LEA associated physiological and psychological risk factors such as within EDE assessment showing lower eating restraint (d = -1.1), eating concern (d = - 0.71) and shape concern (d =-1.2). Within the exercise dependence scale females not at risk of LEA had a higher tolerance of exercise (d = 0.74), time of exercise (d = 0.6) and intentions (d = 0.71). Conclusions: This pilot study highlights that among this sample of amateur-elite athletes, 54% were at risk of LEA (57% female, 50% male). Therefore, there is a need to further investigate and quantify LEA measures within male and female athletes involved in sprinting. This study also identifies that the aetiology of LEA for athletes is complex due to multiple psychological influences identified within the environment of participants.
Keywords: 321006 Sport and exercise nutrition